2021
DOI: 10.1200/jco.2021.39.3_suppl.9
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of anti–PD-1 antibody dostarlimab in patients (pts) with mismatch repair-deficient (dMMR) solid cancers: Results from GARNET study.

Abstract: 9 Background: Dostarlimab is a humanized anti–PD-1 monoclonal antibody that binds the PD-1 receptor, blocking interaction with ligands PD-L1 and PD-L2. The ongoing phase 1 GARNET study (NCT02715284) is evaluating dostarlimab in pts with advanced solid tumors. Here we present safety and efficacy data from cohort F. Methods: Cohort F of the GARNET trial enrolled pts with dMMR or POLEmut non-endometrial solid tumors; the majority were gastrointestinal (GI) in origin. Pts must have progressed per blinded independ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(68 citation statements)
references
References 0 publications
7
48
0
Order By: Relevance
“…The median DOR was not reached and grade ≥ 3 TRAEs were 8%. Within the 69 (65%) mCRC enrolled, ORR was 36.2%, matching the results of other anti-PD-1 antibodies (nivolumab and pembrolizumab) in pre-treated dMMR/MSI-H mCRC [42][43][44]. These results confirm the activity of anti-PD-1 antibodies in pre-treated MSI-High/dMMR mCRC.…”
Section: Highlights In Metastatic Colorectal Cancer Eortc Metastatic Colorectal Cancer Task Force: Thibaud Kössler Francesco Sclafani Marsupporting
confidence: 75%
“…The median DOR was not reached and grade ≥ 3 TRAEs were 8%. Within the 69 (65%) mCRC enrolled, ORR was 36.2%, matching the results of other anti-PD-1 antibodies (nivolumab and pembrolizumab) in pre-treated dMMR/MSI-H mCRC [42][43][44]. These results confirm the activity of anti-PD-1 antibodies in pre-treated MSI-High/dMMR mCRC.…”
Section: Highlights In Metastatic Colorectal Cancer Eortc Metastatic Colorectal Cancer Task Force: Thibaud Kössler Francesco Sclafani Marsupporting
confidence: 75%
“…In addition, post-hoc analysis of KEYNOTE-061 and KEYNOTE-062 suggested remarkable survival benefit for pembrolizumab in MSI-H patients. Most recently, the GARNET study (Cohort F) of dostarlimab (anti-PD-1 antibody) showed ORR of 38.7% in MMR-D patients with non-endometrial solid tumors (ORR of 37.5% for AGC) [ 16 ], leading to FDA accelerated approval to dostarlimab for advanced dMMR solid tumors with VENTANA MMR RxDx Panel. Currently, MSI-H/MMR-D is one of the most consistent predictive biomarkers for ICIs.…”
Section: Clinical Trials Of Immunotherapy For Gastric Cancer With Rel...mentioning
confidence: 99%
“…Another anti-PD-1 antibody, nivolumab, showed a survival benefit in third-line or subsequent treatment in an Asian patient population irrespective of PD-L1 expression (ATTRACTION-2) or in first-line treatment combined with standard cytotoxic agents (CheckMate-649) [ 14 , 15 ]. On the other hand, dostarlimab, an anti-PD-1 antibody, demonstrated a favorable ORR in the GARNET trial in MMR-D patients with non-endometrial solid tumors [ 16 ], and was granted accelerated approval by the FDA. Furthermore, clinical trials of several investigational immunotherapies are ongoing in AGC, including anti-PD-1 antibody plus anti-CTLA4 antibody, ICIs plus other targeted agents, and chimeric antigen receptor T (CAR-T) cell therapies.…”
Section: Introductionmentioning
confidence: 99%
“…The latest addition to the list of tumor agnostic approval is dostarlimab-gxly for adults with MSI high tumors based on the results of GARNET trial. [6] For patients with localized esophageal or esophagogastric junction cancer who have residual disease in the surgical specimen after initial chemoradiotherapy, adjuvant nivolumab for 1 year has been approved recently. [7] Similarly, for renal cell carcinoma, KEYNOTE-564 showed 1 year of adjuvant pembrolizumab improved disease-free survival (DFS) compared with placebo (2-year DFS 77% vs. 68%).…”
Section: International Journal Of Molecular and Immuno Oncologymentioning
confidence: 99%